Analysis of Managerial Conception and Competency of School Heads Background Teachers in Banda Aceh - Rahmat, Zikrur; Irfandi, Irfandi; Pranata, Didi Yudha; Munzir, Munzir; Sarwita, Tuti; Rozailini, Novia; Salbani, Salbani (Teunuleh Publisher, 2023)
This study aims to improve the concept of administration and supervision carried out by providing direction, guidance and a series of motivational activities for teachers related to learning management, staffing, discipleship, building and yard management, financial management, and managing school and community relationships to create an atmosphere which is conducive and fun in a school environment that can provide motivation for teachers in carrying out their duties. The results of the research that have been analyzed show that the principal, who has a sports teacher background, has done his job well as a leader in the school. The principal as a supervisor is intended to increase supervision and control over teachers and other personnel to improve their performance. The principal as a supervisor is in charge of managing all aspects of the curriculum that applies in the school in order to provide results in accordance with predetermined targets. Curriculum aspects that must be mastered by the principal as a supervisor are subject matter, teaching and learning processes, curriculum evaluation, curriculum management, and curriculum development in schools